2013
DOI: 10.11112/jksmi.2013.17.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seismic Performances on Prestressed Composite Coupling Beams with Discontinuous Webs

Abstract: The shear wall system with coupling beams has been known as an effective means for moderate and high rise buildings up to 40 stories, because this structural system can provide the enhanced lateral stiffness compared to individual shear walls. Typical reinforced concrete coupling beams have difficulties in construction due to complicated reinforcing work on site, and steel coupling beams also have disadvantages in economical point of view because of a large number of stiffeners required for its stability under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Their test results indicated that SRC coupling beams with only anchor bolts exhibited more strengths than that calculated with current PCI Code. Oh et al [5] developed the prestressed composite coupling beams and conducted the tests on two prestressed composite coupling beams with different amount of shear reinforcements. Baek [6] proposed the SRC coupling beam with a steel hysteresis damper and investigated experimentally the seismic performance of the special coupling beam.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Their test results indicated that SRC coupling beams with only anchor bolts exhibited more strengths than that calculated with current PCI Code. Oh et al [5] developed the prestressed composite coupling beams and conducted the tests on two prestressed composite coupling beams with different amount of shear reinforcements. Baek [6] proposed the SRC coupling beam with a steel hysteresis damper and investigated experimentally the seismic performance of the special coupling beam.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As shown in Figure 2, the proposed detail of embedment for SRC coupling beams was effective but as the embedment length increase, the strength and stiffness of SRC coupling beam were a little improved. Oh et al [5] introduced the prestressing system into SRC coupling beams to enhance the structural efficiency. Figure 3(a) shows the configuration and reinforcement details of prestressed SRC coupling beams.…”
Section: Structural Performancementioning
confidence: 99%
See 1 more Smart Citation